BLUFF-BODIES VORTEX SHEDDING SUPRESSION BY DIRECT NUMERICAL SIMULATION - Ribeiro, P. A. R.; Schettini, E. B. C.; Silvestrini, J. H. (Revista de Engenharia Térmica, 2004)
Vortex shedding is responsible for harmful vibrations on immersed structures and for increasing their drag coefficients. Thus vortex shedding suppression is highly interesting in order of decrease maintenance costs of standing structures and fuel costs on moving ones. Vortex shedding suppression is here achieved with the use of splitter plates by means of numerical simulations at a low Reynolds range, Re 100 and 160. For this purpose it has been used a high order finite difference method in association with a virtual boundary method, responsible for the obstacles representation. The use of this novel numerical method showed a great concordance with experimental results by means of low computational costs.